Factors influencing aftermarket parts sales in China: the case of an American manufacturer - Bursiek, Chris (Kansas State University, 2013)
The China agricultural equipment market represents 48% of the equipment demand in South East Asia, and 16.5% of the global equipment demand in 2005. With John Deere’s market leadership position in the global agricultural equipment business, in order to maintain that leadership, China will have be part of their plans. John Deere started doing business in China in 1976 and has grown to four agricultural machinery factories in the country. Service parts sales make up an important part of the agricultural equipment business, both in revenue and profit. Margins on service parts sales can be as much as eight times that of new complete good sales. Within China, the John Deere dealer organization in the past has focused primary on selling complete goods, missing out on service parts sales. Successful equipment dealerships outside of China maintain a balance between complete good sales, service parts sales, and service labor sales. The objective of this research was to determine those factors that appear to impact the amount of service parts a John Deere dealership in China sells. Data was collected for three years and regression modeling used to determine what impact variables had on service parts sales and net service parts sales. The outcome of the research found that there are key attributes of John Deere dealerships along with geographical regions that John Deere can focus on in China to improve their service parts sales.
Keywords: Sales; After-market parts; Marketing; Complete goods